IMPLEMENTASI TOPSIS DALAM PEMBERIAN REWARD GURU TERBAIK PADA SMK SWASTA 1 HKBP PEMATANGSIANTAR - Sahat Sonang; Arifin Tua Purba (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Reward is a form of appreciation received by an individual for the achievement of a work performance that aims to motivate the individual to have high productivity. In managerial terms, giving a warning is a good and reasonable thing to do by the leader to his subordinates. Likewise with the Private Vocational School 1 HKBP Pematangsiantar. This research was conducted to provide solutions to problems that occur through the design of a decision support system software for giving the best teacher reward with the Technique for Order Preferences by Similarity to Ideal Solution (TOPSIS) method with assessment components including (1) discipline, (2) involvement, (3 ) attendance, (4) leadership, (5) training and (6) social. The Decision Support System for providing teacher rewards is able to accommodate subjective problems, lack of transparency, and doubts about its accuracy and the output is very credible. Thus the decision-making process for giving the best teacher reward is efficient, effective and objective and can be used as a recommendation for school principals in determining which teachers deserve rewards. From the 10 data samples used, the results of the analysis using the Decision Support System show that the highest recommendation value is 0.7149 on behalf of A8, while the lowest recommendation value is 0.2851 on behalf of A10.